Buxiude fengbei - Tang Dequan,
'Immortal monument'. Printno. J 5366.530. Place of persons, bottom row, f.l.t.r.: Liu Shao-chi, Mao Tse-Tung, Zhu De, Li Dazhao. See also BG E13/209-211, BG E13/404-405, BG E13/448.